Raman resonance tuning of quaterthiophene in filled carbon nanotubes at high pressures. (March 2021) - Alencar, R.S.; Aguiar, A.L.; Ferreira, R.S.; Chambard, R.; Jousselme, B.; Bantignies, J.-L.; Weigel, C.; Clément, S.; Aznar, R.; Machon, D.; Souza Filho, A.G.; San-Miguel, A.; et al.
Abstract: Filling carbon nanotubes with molecules is a route for the development of electronically modified one-dimensional hybrid structures for which the interplay between the electronic structure of molecules and nanotubes is a key factor. Tuning these energy levels with external parameters is an interesting strategy for the engineering of new devices and materials. Here we show that the hybrid system composed by quaterthiophene (4T) molecules confined in single-walled carbon nanotubes, presents a piezo-Raman-resonance of the molecule vibrational pattern. This behavior manifests as a rapid pressure induced enhancement of the 4T Raman mode intensities compared to the tubes G-band Raman modes. Density functional theory calculations allow to explain the spectral behaviour through the pressure-enhanced quaterthiophene resonance evolution. By increasing pressure, the tube cross-section deformation leads to a reduction of the intermolecular distance, to the splitting of the molecular levels and then to an increase of resonance channels. Calculations and experiments converge to the 4T piezo-resonance scenario associated with the pressure-induced nanotube radial collapse observed at about 0.8 GPa. Our findings offer possibilities for the development of pressure transducers based on molecule-filled carbon nanotubes. Graphical abstract: Image 1